2017
DOI: 10.11648/j.ajcem.20170506.17
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Changes in Structural Network in Patients with Nasopharyngeal Carcinoma

Abstract: Radiation therapy (RT) is the standard radical treatment for nasopharyngeal carcinoma (NPC), and has produced excellent effects in terms of survival rate [1,2]. However, one of the serious complications gave rise by the RT is brain injury. Previous studies have found that RT could cause brain structural abnormalities on gray matter and white matter. Nevertheless, the RT effects on the network level should be further investigated. Herein, we explored changes on the structural network for patients with NPC induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The structural connectivity (SC) network is usually considered to be the physical substrate of the functional connectivity (FC) network. In patients with NPC, functional and structural brain network topology change after RT ( Ma et al, 2016 ; Tian and Zhao, 2017 ; Qiu et al, 2018 ; Leng et al, 2019 ; Chen et al, 2020 ). For structural brain networks, a longitudinal DTI study reported that both global and local efficiencies, as well as the nodal topology, were altered in post-RT patients ( Tian and Zhao, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural connectivity (SC) network is usually considered to be the physical substrate of the functional connectivity (FC) network. In patients with NPC, functional and structural brain network topology change after RT ( Ma et al, 2016 ; Tian and Zhao, 2017 ; Qiu et al, 2018 ; Leng et al, 2019 ; Chen et al, 2020 ). For structural brain networks, a longitudinal DTI study reported that both global and local efficiencies, as well as the nodal topology, were altered in post-RT patients ( Tian and Zhao, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with NPC, functional and structural brain network topology change after RT ( Ma et al, 2016 ; Tian and Zhao, 2017 ; Qiu et al, 2018 ; Leng et al, 2019 ; Chen et al, 2020 ). For structural brain networks, a longitudinal DTI study reported that both global and local efficiencies, as well as the nodal topology, were altered in post-RT patients ( Tian and Zhao, 2017 ). This study only investigated the difference between pre-RT and post-RT, but did not consider the different patterns of brain changes at different post-RT periods.…”
Section: Introductionmentioning
confidence: 99%